2016
DOI: 10.1021/acs.energyfuels.6b00869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carboxymethyl Cellulose Binder on the Quality of Biomass Pellets

Abstract: Quality and energy efficiency are two critical concerns associated with the production of biomass pellets. This study elaborates methods to improve the quality of biomass pellets by using a new additive solution (carboxymethyl cellulose (CMC)) and its influence on pellet physical and mechanical properties during the densification of three types of agricultural waste (cotton stalks, wheat straw, and rape straw). Simultaneously, the cohesion and binding mechanisms were analyzed with attenuated total reflectance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…In some recent studies, CMCs have been reported as a cost-efficient binder in biomass pellets that considerably enhanced the quality, durability, and compressive strength of the biomass pellets and reduced the energy consumption extent shells [ 70 , 362 ]. On the other hand, due to the presence of cation-enticed carboxyl groups, CMCs can be hybridized with various metal ions such as Fe 2+ , Ca 2+ , Al 3+ , Mg 2+ , etc., via cross-linking processes to synthesize numerous aerogels with tunable physiochemical and morphological characteristics [ 363 ].…”
Section: Application Of Cmcmentioning
confidence: 99%
“…In some recent studies, CMCs have been reported as a cost-efficient binder in biomass pellets that considerably enhanced the quality, durability, and compressive strength of the biomass pellets and reduced the energy consumption extent shells [ 70 , 362 ]. On the other hand, due to the presence of cation-enticed carboxyl groups, CMCs can be hybridized with various metal ions such as Fe 2+ , Ca 2+ , Al 3+ , Mg 2+ , etc., via cross-linking processes to synthesize numerous aerogels with tunable physiochemical and morphological characteristics [ 363 ].…”
Section: Application Of Cmcmentioning
confidence: 99%
“…Other binders which have been shown to increase the mechanical characteristics of pellets are sugar beet molasses [99], Persea kurzii kosterm powder [100], carboxymethyl cellulose [101], calcium carbonate [102], and cow dung [103]. Cashew nut shell decreases the mechanical characteristics but increases the LHV of pellet of approximately 1 and 0.5 cal•g −1 in comparison with the use of Persea and dammar as binders, respectively.…”
Section: Effects Of Blending and Binders On Pellet Qualitymentioning
confidence: 99%
“…To the best of our knowledge, there is no ISO standard for energy consumption for pelletization. However, many researchers have focused on this index [24,25,33,47,50,[59][60][61]. According to Equation (1), the curve of the force (F 1 , F 2 ) and displacement (x 1 , x 2 ) can be obtained by a single pelletizer.…”
Section: Effects Of Different Factors On Energy Consumption Of Pelletmentioning
confidence: 99%
“…As reviewed in Figure 8, during the pelletization process, the average energy consumption of wood pellets is around 40 kJ/kg, and the energy consumption of straw pellets is generally in the range of 13-25 kJ/kg. That is, the energy consumption of wood pellets is much higher than that of straw pellets, which is mainly because straw plants contain more cellulose and hemicellulose [61]. These natural binders are easier to form and agglomerate, resulting in lower energy consumption for the pelletization of straw [65].…”
Section: Effects Of Different Factors On Energy Consumption Of Pelletmentioning
confidence: 99%